2018
DOI: 10.1111/jftr.12262
|View full text |Cite
|
Sign up to set email alerts
|

The Central Roles of Race and Racism in Reframing Family Systems Theory: A Consideration of Choice and Time

Abstract: This article explores the central roles in family research and practice of race and racism in the reframing of family systems theory (FST) when applied to Black and/or African American families. Specifically, we discuss how current concepts of FST allow for an understanding of racial and ethnic socialization in the parent–child familial subsystem. We then theorize the potential reframing of FST to better accommodate race, ethnicity, and racism, and suggest an expansion of the theory by including the components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 72 publications
1
49
0
Order By: Relevance
“…For example, Mandara and Murray's () research demonstrated that African American boys whose fathers were absent from home had a higher risk for mental health and behavioral problems than did African American boys whose fathers were present. WTSU reinforces also the argument of James et al ():
Turning a blind eye to racism or how a color‐blind ideology may affect some Black families would prevent scholars and practitioners from completely understanding reasons that some Black families tend to be structured the way they are and reasons they engage in certain patterns of behaviors. (p. 420)
It is also clear throughout the series that the five boys and their families lacked “resource characteristics” to support optimal proximal processes in their microsystems, as when the boys and their families struggle to understand why their sons are being arrested, how to manage bond payments, and finally acquire adequate legal representation.…”
Section: Policy Structural Racism and Family Lifesupporting
confidence: 52%
See 2 more Smart Citations
“…For example, Mandara and Murray's () research demonstrated that African American boys whose fathers were absent from home had a higher risk for mental health and behavioral problems than did African American boys whose fathers were present. WTSU reinforces also the argument of James et al ():
Turning a blind eye to racism or how a color‐blind ideology may affect some Black families would prevent scholars and practitioners from completely understanding reasons that some Black families tend to be structured the way they are and reasons they engage in certain patterns of behaviors. (p. 420)
It is also clear throughout the series that the five boys and their families lacked “resource characteristics” to support optimal proximal processes in their microsystems, as when the boys and their families struggle to understand why their sons are being arrested, how to manage bond payments, and finally acquire adequate legal representation.…”
Section: Policy Structural Racism and Family Lifesupporting
confidence: 52%
“…WTSU tackles the exosystemic effect of policies that sparked mass incarceration that shape the experiences and family life of African Americans. James et al () argued that “law enforcement policies (e.g., drug sentencing guidelines, stop‐and‐frisk policing, law‐and‐order movement, government‐supported prison‐industrial complex) over the past 50 years have undergirded the exponential growth in the prison population, which consists of a disproportionate number of African American men and women” (p. 425). It is important to note that discriminatory policies have had significant implications for African American family life.…”
Section: Policy Structural Racism and Family Lifementioning
confidence: 99%
See 1 more Smart Citation
“…James, Coard, Fine, and Rudy () argued that historical events influence contemporary family interactions and the choices families make about actions they take. Black individuals have some of the lowest levels of banking participation among ethnic/racial minority groups in the United States (Blanco, Angrisani, Aguila, & Leng, ), which may be attributed to a lack of trust developed from past experience.…”
Section: Overviewmentioning
confidence: 99%
“…Unfortunately, not participating in banking, though understandable, can have negative consequences for Black families' wealth and implications for the racial wealth gap. This is heightened when considering that White families received indirect government assistance in building wealth (e.g., redlining; James et al, ) or were able to build wealth through their banking with White‐owned banks that built wealth off the deposits of Black families and Black banks (Baradaran). Regardless, neoclassical economists are still likely to argue that, regardless of that history, Black Americans' financial choices are merely evidence of the freedom to choose what they believe is best for them and/or their families (Sowell, ).…”
Section: Overviewmentioning
confidence: 99%